2020
DOI: 10.1088/1742-6596/1470/1/012008
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a test instrument to measure pre-service mathematics teachers’ content knowledge and pedagogical content knowledge

Abstract: Teacher education in Indonesia aims to prepare pre-service teachers in becoming professional teaching personnel. Two important knowledge need to be acquired are content knowledge (CK) and pedagogical content knowledge (PCK). However, it is still a challenge to measure the pre-service mathematics teachers’ CK and PCK. Therefore, the first aim of the present study is to develop and validate a test instrument to measure CK and PCK of pre-service mathematics teachers on high school level mathematics. Second, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Pedagogic competence includes implementing conducive mathematics learning based on the curriculum up to implementing learning to the evaluation stage of students [7,8]. In addition to pedagogic understanding, teachers or prospective teachers are also required to have good content knowledge [71][72][73][74].…”
Section: Discussionmentioning
confidence: 99%
“…Pedagogic competence includes implementing conducive mathematics learning based on the curriculum up to implementing learning to the evaluation stage of students [7,8]. In addition to pedagogic understanding, teachers or prospective teachers are also required to have good content knowledge [71][72][73][74].…”
Section: Discussionmentioning
confidence: 99%
“…Preservice mathematics teachers' PCK and content knowledge (CK) were tried to measure by using a test instrument. It employed the developmental research method and used students' empirical data to investigate the instrument's validity, objectivity, and reliability (Kristanto et al, 2020;Salakhova et al, 2021). It was found that there was no significant correlative relationship between pre-service secondary teachers' CK and PCK and results further revealed that their knowledge of content and students was weak (Sintema et al, 2020).…”
Section: The Components Of Pckmentioning
confidence: 99%
“…Content and pedagogic knowledge will make it easier for teachers to develop valid instruments in measuring students' mastery of material (Kristanto, Panuluh & Atmajati, 2020). Teachers' HOTS skills also determine how they transfer HOTS to their students (Misri, 2020).…”
Section: Hots-based Test Instrumentmentioning
confidence: 99%